Formulasi Food Bar Sebagai Pangan Darurat Berbasis Tepung Ubi Jalar Oranye (Ipomoea Batatas L.) Dan Tepung Kacang Merah (Phaseolus Vulgaris L.) - Noli Novidahlia; Siti Maulida Ulfa; Titi Rohmayanti (JURNAL AGROINDUSTRI HALAL, 2022)
Food is the most needed necessity in an emergency situation such as natural disaster. The application of local food like orange sweet potatoes and red beans in producing food bar as the emergency food is one of the efforts to establish the food security. The purpose of this research is determine the ratio of orange sweet potato flour and red bean flour to the nutritional value and characteristics of food bars for emergency food. Food bars are selected based on their nutritional value and total calories produced. The selected food bar is formulation which consists of 10% orange sweet potato flour and 30% red bean flour. The results of the analysis of the nutritional value of 50g food bar resulted in water content 4.17g, ash content 1,41 g, fat content 7.32g, protein content 4.86g, carbohydrate content 32.36g, beta-carotene content 6.61mg/50g, total calories 214.34 Kcal, and hardness 3054.50 g/f. The results of the sensory quality unpleasant smell, a hard texture, and sweet taste.